Perancangan Rangka Mesin Press Hidrolik Kapasitas 50 Ton - M, Riki Fredrik H; Herisiswanto, Herisiswanto; Cupu, Dedi Rosa Putra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Press machine is a machine design to produce a high pressure, which is applied to facilitate human work such as destroying an object, push or lift it. The power source can come from the hydraulic machines, human power, electric motors and others. The purpose of this study was to obtain the results of design of the framework of press machine in form of technical drawings and analysis of strength of the structure. This research is limited by loading of 50 tons. The research was began with data collection, design, then technical drawing and final design. The material in this research used St 50. Based calculations result was performed the stress that occurs in the cylinder holder of 3.4 N / mm2, on the table is 2.6 N / mm2. The deflection was occurred in the cylinder stand of 0.017 mm, on the table is 0.54 mm. Keywords: Press machine, Frame design, Hydraulic system, Technical drawings